2022
DOI: 10.1038/s41388-022-02253-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblast-induced lncRNA UPK1A-AS1 confers platinum resistance in pancreatic cancer via efficient double-strand break repair

Abstract: The tumor stroma of pancreatic ductal adenocarcinoma (PDAC) is characterized by an abundant and heterogeneous population of cancer-associated fibroblasts (CAFs), which are critically involved in chemoresistance. However, the underlying mechanism of CAFs in chemoresistance is unclear. Here, we show that CAFR, a CAF subset derived from platinum-resistant PDAC patients, assumes an iCAF phenotype and produces more IL8 than CAFS isolated from platinum-sensitive PDAC patients. CAFR-derived IL8 promotes oxaliplatin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Zhang et al also reported that higher IL-8 production by PDAC CAFs is correlated with oxaliplatin resistance in these patients. The underlying mechanism of this chemoresistance was attributed to the upregulation of UPK1A-AS1 lncRNA via IL-8 signaling, which in turn enhances DNA double-strand break (DSB) repair by strengthening the binding between Ku70 and Ku80 (52). Furthermore, it has been reported that CAFs can induce 5-FU resistance in colorectal cancer through cargo delivery of secreted exosomes (53).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al also reported that higher IL-8 production by PDAC CAFs is correlated with oxaliplatin resistance in these patients. The underlying mechanism of this chemoresistance was attributed to the upregulation of UPK1A-AS1 lncRNA via IL-8 signaling, which in turn enhances DNA double-strand break (DSB) repair by strengthening the binding between Ku70 and Ku80 (52). Furthermore, it has been reported that CAFs can induce 5-FU resistance in colorectal cancer through cargo delivery of secreted exosomes (53).…”
Section: Discussionmentioning
confidence: 99%
“…Platinum-based chemotherapy is a first-line chemotherapy treatment for patients with advanced pancreatic cancer; however, the overall response rate is only 30% worldwide ( 21 ). Our previous study reported that cancer-associated fibroblasts promote the acquired oxaliplatin resistance of pancreatic cancer cells via paracrine signaling ( 22 ). However, there are few studies on the inherent oxaliplatin resistance of pancreatic cancer tumor cells ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…LINC01426 knockdown dramatically decreased pancreatic cancer cell growth in vivo. S e v e r a l c l i n i c a l a n d b a s i c i n v e s t i g a t i o n s h a v e demonstrated that lncRNAs are implicated in molecular mechanisms (16)(17)(18). Some lncRNAs regulate the incidence and development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and basic investigations have demonstrated that lncRNAs are implicated in molecular mechanisms ( 16 - 18 ). Some lncRNAs regulate the incidence and development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%